Evaluating Organizational Capacity Development - Mackay, Ronald; Horton, Douglas; Dupleich, Luis; Andersen, Anders (University of Toronto, 2002)
Abstract: While substantial sums are being invested in the development of organizational and institutional capacities, the design and management of capacity development efforts leave much to be desired. Few capacity development initiatives have been systematically and thoroughly evaluated. This article describes the conceptual frameworks and methods used to evaluate a multisite, regional capacity-development project in Latin America and the Caribbean undertaken to strengthen planning, monitoring, and evaluation in agricultural research organizations. The article discusses some of the challenges facing capacity development and its evaluation, outlines the procedures employed, and illustrates these with some consolidated findings in response to four evaluation questions: What were the main contributions of the project to agricultural research management? How were the results achieved? What factors facilitated their achievement? and What lessons can we learn to improve future capacity development efforts and their evaluation?